(3cJGH GdWHs - (3GHf GdLRGQ , CMeO Hf EHQGgje Hf CHj NGdO GdbjQhGfj, CHh LYaQ,J (B369 (3g` s
(3ChdgG (B:s
(3cJGH eLehY ef cJH GdChGFd ai YdGL GdabQGA hGdeSGcjf HGdCOhjI GdJi JSgd hLhOgG eeG YfG HLeYg s
(3BNQgG (B:s
(3hbO PcQfG ai cJGH RGO GdeSGaQ YdGL LejY GdCeQGV hGdYdd GdJi PcQfGgG CNJUQfG ai gPG GdcJGH YdGL GdYdd HGdCOhjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B137s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs